Embracing new paths in visual research facilitation: opportunities, tensions & ethical considerations. Issue 1 (15th March 2022) - Burkholder, Casey; Aladejebi, Funké; Schwab-Cartas, Josh
Abstract : This introduction to the special section establishes facilitation as an important yet underreported component of visual sociological research. Although institutional and regulatory ethics have been ingrained in university research settings, scholars such as Eve Tuck and K. Wayne Yang (2014 ) have asked us to consider the ways in which participants' and communities' refuse research influence our ethical frameworks. We take up Tuck and Yang's call to ask: What does ethical research facilitation look like beyond institutional guidelines in visual research? What might deep, ethical, meaningful or useful facilitation look like in visual studies? Putting social justice concerns about power within research processes at the fore, the editorial argues that thinking through research facilitation must go beyond researcher reflexivity, and move towards action within the research settings in which we work.